2010
DOI: 10.1148/radiol.10091759
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis of the Hand: Monitoring with a Simplified MR Imaging Scoring Method—Preliminary Assessment

Abstract: This simplified reproducible scoring scheme could be used to monitor joint damage in rheumatoid arthritis. (c) RSNA, 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
0
24
0
3
Order By: Relevance
“…SAMIS correlated well with the traditional RAMRIS score with correlation coefficients between 0.8 and 0.9 and reduced the time needed by about two-thirds to 2-7 min depending on the complexity of the changes. Interestingly, interobserver agreement was similar for erosions but higher for SAMIS than RAMRIS for synovitis and edema [36]. It will be important to compare SAMIS with radiographic scoring in the future.…”
Section: Imagingmentioning
confidence: 93%
See 1 more Smart Citation
“…SAMIS correlated well with the traditional RAMRIS score with correlation coefficients between 0.8 and 0.9 and reduced the time needed by about two-thirds to 2-7 min depending on the complexity of the changes. Interestingly, interobserver agreement was similar for erosions but higher for SAMIS than RAMRIS for synovitis and edema [36]. It will be important to compare SAMIS with radiographic scoring in the future.…”
Section: Imagingmentioning
confidence: 93%
“…However, again scoring methods require much time. Cyteval et al [36] have developed a Simplified RA Magnetic Resonance Imaging Score (SAMIS) that focuses on only one hand and few regions but still determines erosions, synovitis and bone marrow edema. SAMIS correlated well with the traditional RAMRIS score with correlation coefficients between 0.8 and 0.9 and reduced the time needed by about two-thirds to 2-7 min depending on the complexity of the changes.…”
Section: Imagingmentioning
confidence: 99%
“…The ESPOIR cohort has not only provided information on radiographic disease progression over time [3], but also shown that oblique radiographs of the feet are superior over anteroposterior radiographs for detecting bony erosions in recent-onset RA [29]. A simplified MRI score has been developed to assist in the evaluation of hand joint lesions in recent-onset RA [30]. Proof has been obtained that ultrasonography contributes to the early diagnosis and prognostic evaluation in RA [31][32][33].…”
Section: Imagingmentioning
confidence: 99%
“…Rheumatoid Arthritis Magnetic Resonance Imaging Score (or RAMRIS) was developed as a reference standard with which to assess RA later; however, it was time consuming and required a long learning curve (81,82). Cyteval et al (83) proposed a simplified MR imaging scoring method that was closely correlated with the Rheumatoid Arthritis Magnetic Resonance Imaging Score.…”
Section: Sodium Imagingmentioning
confidence: 99%